HUBUNGAN TINGKAT PENGETAHUAN COVID-19 TERHADAP KECEMASAN MAHASISWA KEPERAWATAN YANG PRAKTIK DI RUMAH SAKIT - Adlei Brynt Yosafat Hutagalung; Ernawati Siagian (NUTRIX, 2021)
Abstract Article Title. COVID-19 has the potential of a high death rate as it is very contagious and it could spread within a very little amount of time. The current COVID-19 pandemic has impacted changes in aspects of life, including inflicting anxiety. Anxiety can be found in anyone including postgraduate students. Due to the lack of understanding and knowledge, it has become one of the factors the cause anxiety in nursing students during clinical practice. The purpose of this study was to identify the correlation in the level of knowledge towards anxiety among nursing students, who are currently doing medical practices, in hospitals. The method in this research is correlational descriptive by using a non-probability sampling technique of 105 respondents. Hamilton Anxiety Rating Scale (HARS) will be used to measure the anxiety levels and knowledge on COVID-19. The univariate analysis will be implemented to process data by using frequency and presentation. Bivariate analysis is done by Spearman Rho. Results of the collected data showed that 86 respondents (81.9%) has an excellent level of knowledge while 19 respondents (18.10%) has a satisfactory level of knowledge. Other than that, it has been found that 75 respondents (71.43%) do not have anxiety, 24 respondents (22.86%) has light anxiety and three respondents (2.86%) have moderate to severe anxiety. Analysis showed that there is no significant relationship between gender and knowledge with a sig value = 0.521 (p > 0.05). There is no significant relationship between gender and anxiety with a sig value = 0.079 (p > 0.05). There is no significant relationship between level of education and knowledge with a sig value = 0.807 (p > 0.05). There is a significant relationship between level of education and anxiety with the sig value = 0.019 (p > 0.05). There is no significant relationship between knowledge and anxiety with the sig value = 0.214 (p > 0.05). Correlational value is found to be -0.122, which means there is a relationship that contrasts with the very weak level of closeness. By giving information and medical knowledge to postgraduate students by sharing resources and facilities to address anxiety could improve behavior, attitude, and medical practices within the nursing students in correlation to prevent the spread of COVID-19. Abstrak COVID-19 merupakan potensi kematian yang cukup besar saat ini karena penyebaran yang begitu cepat. Pandemi virus COVID-19 saat ini berdampak pada perubahan aspek kehidupan, termasuk mengakibatkan munculnya kecemasan. Kecemasan dapat menyerang siapa pun termasuk mahasiswa. Kurangnya pengetahuan merupakan salah satu faktor yang menyebabkan kecemasan pada mahasiswa keperawatan saat menjalani praktik klinik. Tujuan penelitian ini yaitu mengetahui hubungan antara tingkat pengetahuan terhadap kecemasan mahasiswa keperawatan yang praktik di Rumah Sakit. Metode penelitian yaitu deskriptif korelasional dengan menggunakan teknik non probability sampling yang berjumlah 105 responden. Hamilton Anxiety Rating Scale (HARS) digunakan untuk mengukur tingkat kecemasan dan tentang pengetahuan COVID-19. Data dianalisis secara univariat dengan menggunakan frekuensi dan presentasi. Analisa secara bivariat dengan Spearman Rho. Hasil menunjukkan bahwa tingkat pengetahuan berada berada pada kategori baik (81,90%) dengan 86 responden dan pada kategori cukup (18,10%) dengan 19 responden. Selain itu juga ditemukan bahwa responden yang tidak mengalami kecemasan (71,43%) dengan 75 responden, yang mengalami kecemasan ringan (22,86%) dengan 24 responden dan yang mengalami kecemasan sedang dan berat (2,86%) dengan 3 responden. Analisis menunjukkan bahwa Tidak terdapat hubungan yang signifikan antara jenis kelamin dan pengetahuan dengan nilai sig = 0,521 (p > 0,05). Tidak terdapat hubungan yang signifikan antara jenis kelamin dan kecemasan dengan nilai sig = 0,079 (p > 0,05). Tidak terdapat hubungan yang signifikan antara tingkat pendidikan dan pengetahuan dengan nilai sig = 0,807 (p > 0,05). Terdapat hubungan yang signifikan antara tingkat pendidikan dan kecemasan dengan nilai sig = 0,019 (p > 0,05). Tidak terdapat hubungan yang siginifkan antara pengetahuan dan kecemasan dengan nilai sig = 0,214 (p > 0,05). Nilai korelasi yang didapatkan -0,122 berarti ada hubungan yang berlawanan arah dengan tingkat keeratan sangat lemah. Memberikan informasi dan pengetahuan kesehatan kepada mahasiswa melalui berbagai sumber dan sarana dimaksudkan untuk menangani kecemasan serta meningkatkan perilaku, sikap, dan praktik keperawatan mahasiswa berkaitan dengan pencegahan dan pengendalian COVID-19.